Exploration of organ morphogenesis Ⅰ: Bioelectricity and morphogenesis - Zhao Haiping; Liu Zhen; Chen Guangxin; Li Chunyi (浙江大学学报. 农业与生命科学版, 2015)
Morphogenesis is a biological process that involves the shape development and pattern maintenance of an organism. Morphogenetic information is needed for morphogenetic primordial developing to construct an appropriate three-dimension (3D) structure, which includes three aspects: positional information, prepatterning information, and epigenetic information. The essence and mechanism of morphogenetic information is the primary condition to understand morphogenesis. This paper reviews the latest research progress of morphogenetic field, bioelectricity and organ morphogenesis.Mechanism of organ morphogenesis has not been well understood in life science field. Advances in molecular biology were expected to solve this mystery, but proved to be a failure. Interestingly, recent study showed that organ morphogenesis was regulated by bioelectricity at multiple levels on lower animals, for example: 1) Artificially setting the resting potential in embryonic frog cells can lead to eye formation at any part of amphibian body; 2) bioelectricity can regulate regeneration of tail and ectopic limb formation in Xenopus tadpoles; 3) bioelectricity determines regeneration pattern of amputated planaria fragments on whether head or tail. Therefore, organ fate was obviously determined by bioelectric state of morphogenetic primordia. Bioelectricity is the essence of organ morphogenetic information, which is a landmark advance in this field that the bioelectricity encodes organ morphogenesis.It is an inspiration that electric is used as a signal code in communication for understanding work mechanism of bioelectric code. For example, Morse alphabet and binary, which consist of electrical signal, are used in telegram system and computer system respectively. Nowadays, 3D structures can be made by 3D printer, and the machine can execute commands encoded by binary. The physical process of bioelectricity encoding organ morphogenesis in animal bodies is similar with that of 3D structures made by printer. On basis of those theories, a hypothesis was proposed that complicated bioelectric mode (BM) operation in animal bodies was similar with binary in computer system. Exploration of the signal pathway of BM is the key to crack bioelectricity code. The dream of artificially controlling organ morphogenesis was expected to be realized when the secret code of bioelectricity for organ morphogenesis be cracked in the near future.